2019
DOI: 10.1111/lam.13201
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous anodic alumina reduces Staphylococcus biofilm formation

Abstract: Staphylococcus epidermidis and Staphylococcus aureus, two bacterial strains commonly associated with biofilm‐related medical infections and food poisoning, can rapidly colonize biotic and abiotic surfaces. The present study investigates the ability of anodic alumina surfaces with nanoporous surface topography to minimize the attachment and biofilm formation mediated by these pathogenic bacterial strains. Early attachment and subsequent biofilm development were retarded on surfaces with nanopores of 15–25 nm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(53 reference statements)
2
3
0
Order By: Relevance
“…The authors noted that the "hillocks" nanotopography (~50 nm in diameter) and surface hydrophobicity (akyl-terminated monolayer) each enhanced bacterial attachment and colonization, but quantification of the interactions was not reported. However, we observed that the smaller pore surfaces (AAO15 and AAO25), being rougher than NS, reduced biomass compared with the NS control, which is in good agreement with our previous reports 7,19,53 . This apparent contradiction in the biomass trends with regard to roughness once again underscores the necessity of characterizing the exact details of nanotopography beyond simple roughness measurements 54 .…”
Section: Bacteriasupporting
confidence: 93%
See 2 more Smart Citations
“…The authors noted that the "hillocks" nanotopography (~50 nm in diameter) and surface hydrophobicity (akyl-terminated monolayer) each enhanced bacterial attachment and colonization, but quantification of the interactions was not reported. However, we observed that the smaller pore surfaces (AAO15 and AAO25), being rougher than NS, reduced biomass compared with the NS control, which is in good agreement with our previous reports 7,19,53 . This apparent contradiction in the biomass trends with regard to roughness once again underscores the necessity of characterizing the exact details of nanotopography beyond simple roughness measurements 54 .…”
Section: Bacteriasupporting
confidence: 93%
“…We first focus on the effect of nanotopography alone on biofilm accumulation. Consistent with our previous studies 7,8,19 , bacterial presence on the uncoated small nanopores (AAO15 and AAO25) was substantially reduced compared with either the uncoated large pores (AAO100) or NS controls, for all bacteria. Both visual inspections and quantitative evaluations of biomass indicate that the extent and morphology of biomass also varied noticeably among the tested bacteria.…”
Section: Impact Of One Approach On Surface Biomass Accumulationsupporting
confidence: 91%
See 1 more Smart Citation
“…A similar hydration layer strategy was employed by Feng et al. (2019) without using polymers, where these researchers prepared textured alumina surfaces by anodization. The anodization process resulted in nanotextured alumina.…”
Section: Repulsion‐based Antifouling Surfacesmentioning
confidence: 99%
“…Studies in the past decade have demonstrated early promises for sublithographic patterning by electron beam lithography and directed self-assembly techniques (e.g., block copolymers, nanoparticles, and anodization). In addition to the nanoscale surface patterns, nanostructures fabricated using bulk materials, such as the nanopores in anodic aluminum oxide (AAO), offer a useful platform for studying bacteria–surface interactions. ,, Existing anodic etching protocols have produced hexagonally arranged nanopores (circular, triangular, or squarely shaped) with tunable aspect ratios (e.g., diameter, 6–500 nm; pore length, tens of nm to hundreds of μm) ,, distributed over macroscopic areas (on the order of cm 2 to m 2 ), without requiring a clean room. The chemical stability of aluminum oxide also provides a resilient foundation for subsequent engineering of surface chemistry and biofunctionality, for understanding decoupled effect of surface properties on bacterial behaviors, as discussed below.…”
Section: Research Needs In Understanding Fundamental Bacteria–surface...mentioning
confidence: 99%